Multi‐objective contractor’s ranking by applying the Moora method - Brauers, Willem Karel M.; Zavadskas, Edmundas Kazimieras; Turskis, Zenonas; Vilutienė, Tatjana (Journal of Business Economics and Management, 2008)
Construction, taking off, maintenance and facilities management of a building is a typical example of consumer sovereignty: the new owner likes to have a reasonable price to pay, to have confidence in the contractor, to know about the duration of the works, the service after completion and the quality of the work. On the other side the contractor has his objectives too, like the satisfaction of the client, diminishing of external costs and annoyances and the management cost per employee as low as possible. In other words it concerns a problem of multi‐objectives. Therefore a final ranking will show the best performing contractor from the point of view of the clients but also from the point of view of the contractors themselves. The MOORA method based on ratio analysis and dimensionless measurement will accomplish the job of ranking the contractors in a non‐subjective way. As an application the largest maintenance contractors of dwellings in Vilnius, capital of Lithuania, were approached. First published online: 14 Oct 2010